2019
DOI: 10.1186/s12889-019-7774-1
|View full text |Cite
|
Sign up to set email alerts
|

‘If I donate my organs it’s a gift, if you take them it’s theft’: a qualitative study of planned donor decisions under opt-out legislation

Abstract: BackgroundThere is a worldwide shortage of donor organs for transplantation. To overcome this, several countries have introduced an opt-out donor consent system. This system, soon planned for Scotland and England means individuals are automatically deemed to consent for organ donation unless they register an opt-out decision. This study was designed to explore the reasons underpinning donor choices for people who plan to actively opt-in to the register, take no action and be on the register via deemed consent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 27 publications
3
47
1
1
Order By: Relevance
“…(2014). Although this result may seem surprising, experimental research suggests that opt-in policies portray donation as an active, altruistic act (Davidai et al ., 2012; Miller et al ., 2019). This portrayal aligns with the norm of giving as an active process that exists in countries where philanthropy is high (Shepherd et al ., 2014).…”
Section: Discussion and Remarksmentioning
confidence: 99%
“…(2014). Although this result may seem surprising, experimental research suggests that opt-in policies portray donation as an active, altruistic act (Davidai et al ., 2012; Miller et al ., 2019). This portrayal aligns with the norm of giving as an active process that exists in countries where philanthropy is high (Shepherd et al ., 2014).…”
Section: Discussion and Remarksmentioning
confidence: 99%
“…Being registered to donate organs under either an opt-in or opt-out system involves psychological costs 30,31 . These costs stem from considering one's morality, perceived violations of bodily integrity, medical mistrust at how one may be treated by the medical profession in life-threatening situations (e.g., harvesting organs before death), the 'ick' factor (i.e., donating organs feels disgusting), the 'jinx' factor (i.e., registering makes one more likely to die) and a preference for individual over state ownership.…”
Section: Opt-out Vs Opt-in and The Role Of Lone Wolves And Good Shephmentioning
confidence: 99%
“…In a recent survey of 1202 members of the UK public about their thoughts on the introduction of the 'opt-out' organ donation system, researchers from the University of Stirling found that current NHS myth-busting campaigns, which focussed principally on dissemination of facts, were less effective than 'narrative communication campaigns that employ fictional testimonies to refute organ donation myths'. Campaigns containing personal narratives have been shown to increase donor intentions (Miller, Currie, & O'Carroll, 2019b). Those who tend to have favourable attitudes towards organ donation are medical staff who have more insight into the subject of donation, but this is not representative of the general population (Coad et al, 2013;Flod en & Forsberg, 2009).…”
Section: Organ and Body Donation Attitudesmentioning
confidence: 99%
“…Organisations such as Hospice UK (https://www.hospiceuk.org/) are aiming to change public attitudes and behaviour around dying, death and bereavement through online campaigns such as 'Dying Matters' (https:// www.dyingmatters.org/) and 'Awareness Week' but the topic of donation is not included in their campaigns. Under the new opt-out organ donation system, it is the role of 'the families to confirm the deceased's objection to donation, otherwise consent is deemed' (Miller, Currie, & O'Carroll, 2019b). It is, therefore, increasingly important for people to discuss their wishes with their relatives (Coad, Carter, & Ling, 2013) especially with those who are fearful of the topic.…”
Section: Introductionmentioning
confidence: 99%